Social Support Modulates Neural Responses to Unfairness in the Ultimatum Game - Wei, Chunli; Zheng, Li; Che, Liping; Cheng, Xuemei; Li, Lin; Guo, Xiuyan (Frontiers in Psychology, 2018)
The current functional MRI study aimed to investigate how responders’ fairness considerations and related decision-making processes were affected by social support in the ultimatum game (UG). During scanning, responders either played the standard UG with proposers (control condition) or played the modified UG in which three unknown observers showed social support for responders by acknowledging proposers’ norm violation. Results revealed that participants reported higher unfairness feelings and rejection rates of unfair offers in the social support condition relative to the control condition. At the neural level, compared to the control condition, perception of social support from others induced greater activations of anterior cingulate gyrus and right anterior insula when receiving unfair (vs. fair) offers. The medial prefrontal cortex and right anterior insula were more active when the unfair offers were rejected (vs. accepted) in the social support condition than the control condition. These results highlighted the modulation effect of social support on responders’ fairness considerations and related decision-making processes.